ZnT8 loss of function mutation increases resistance of human embryonic stem cell-derived beta cells to apoptosis in low zinc condition - Sui, Lina (2023)
The rare SLC30A8 mutation encoding a truncating p.Arg138* variant (R138X) in zinc transporter 8 (ZnT8) is associated with a 65% reduced risk for type 2 diabetes. To determine whether ZnT8 is required for beta cell development and function, we derived human pluripotent stem cells carrying the R138X mutation and differentiated them into insulin-producing cells. We found that human pluripotent stem cells with homozygous or heterozygous R138X mutation and the null (KO) mutation have normal efficiency of differentiation towards insulin-producing cells, but these cells show diffuse granules that lack crystalline zinc-containing insulin granules. Insulin secretion is not compromised in vitro by KO or R138X mutations in human embryonic stem cell-derived beta cells (sc-beta cells). Likewise, the ability of sc-beta cells to secrete insulin and maintain glucose homeostasis after transplantation into mice was comparable across different genotypes. Interestingly, sc-beta cells with the SLC30A8 KO mutation showed increased cytoplasmic zinc, and cells with either KO or R138X mutation were resistant to apoptosis when extracellular zinc was limiting. These findings are consistent with a protective role of zinc in cell death and with the protective role of zinc in T2D.